Ways and means of expressing verbal aggression in modern Russian communication - Sergeevna, Yanchenkova Irina (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the genres of verbal aggression common in modern Russian communication. The author describes the ways and means of representation of verbal aggression, reveals their functional-semantic and communicative-pragmatic properties, and determines the causes of aggressive speech behavior of communicators. The materials of the article are of practical value for linguists, lawyers engaged in forensic linguistic expertise on the material of Russian speech.